The Impact of Transformational Leadership and Intrinsic Motivation on Teacher Performance via Job Satisfaction: A Structural Equation Modeling (SEM) with Partial Least Squares (PLS) Analysis - Ompusunggu, Nommensen Pangihutan; Ruspitasari, Widi Dewi; Handoko, Yunus (Jurnal Paedagogy, 2025)
This study investigates the mediating effect of job satisfaction on the relationship between situational leadership and motivation on teacher performance. A quantitative approach was employed, and the research was conducted at Santo Nicholas School, Medan, with all teachers participating as the sample. Data were collected using a six-point Likert survey and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that situational leadership has no significant direct or indirect impact on teacher performance, whereas motivation has a significant effect on performance through both direct and indirect paths. Job satisfaction partially mediates the relationship between motivation and performance, but it does not mediate the relationship between situational leadership and performance. The findings emphasize the importance of motivational support in enhancing job satisfaction and teacher performance.